Effect of Lecithin on Dermal Safety of Nanoemulsion Prepared from Hydrogenated Lecithin and Silicone Oil - Duck-Hwan Bae; 신재섭; Gwi-Su Shin; Fan-Long Jin; 박수진 (Bulletin of the Korean Chemical Society, 2009)
In this study, a hydrogenated lecithin-containing nanoemulsion was prepared from hydrogenated lecithin and silicone oil. Tween-60 and liquid paraffin, widely known emulsifiers, were used as standard substances, and high shear was produced by utilizing a high shear homogenizer and microfluidizer. The properties of the nanoemulsion prepared with hydrogenated lecithin were evaluated by measuring interfacial tension, dynamic interfacial tension, droplet size, zeta-potential, friction force, skin surface hygrometery, and dermal safety. The interfacial tension of lecinol S10/silicone oil was lower than that of lecinol S10/liquid paraffin. The nanoemulsion prepared from hydrogenated lecithin shows lower zeta-potential, skin surface hygrometery, and friction force compared with a general emulsion. The silicone nanoemulsion prepared from hydrogenated lecithin showed a zero value in the patch test and thus exhibits high dermal safety. KCI Citation Count: 5